Analysis The Effect of Net Exports and The Exchange Rate On Indonesia's Foreign Exchange Reserves in 1990-2020 - Rasika Dhuita Haya Minhaj; Ickhsanto Wahyudi (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2022)
The research aims to determine the effect of net exports and the exchange rate on Indonesia's foreign exchange. The sample in this study is data on net exports, the exchange rate, and Indonesia's foreign exchange reserves in 1990-2020. Data used in this study come from the Bank of Indonesia and the Central Bureau of the Statistics Republic of Indonesia. The data were analyzed using a correlation test and descriptive statistical analysis. The data analysis technique used is multiple regression analysis techniques to obtain a comprehensive picture of the relationship between one variable and another. And also use F-test, T-test, and determination coefficient test to test the hypothesis. The research results show that simultaneously net exports and the exchange rate affect Indonesia's foreign exchange reserves.  Partially, net exports and the exchange rate significantly affect Indonesia's foreign exchange reserves.